The Myth of Triumphalism : Rethinking President Reagan's Cold War Legacy - Fischer, Beth A., 1964- (Book collections on Project MUSE., 2020)
"Did President Reagan's hawkish policies destroy the Soviet Union and enable the United States to win the Cold War? Many Americans believe this to be the case. In this view -- known as 'triumphalism' -- Reagan's denunciations of the 'evil empire' and his military buildup compelled Moscow to admit defeat. The president's triumph demonstrates that America's leaders should stand strong and threaten adversaries into submission. Drawing on both US and Soviet sources, this study demonstrates that triumphalism is a series of falsehoods about President Reagan's intentions, his policies, and the impact his administration had on the Soviet Union. In reality, the president's initially hardline posture undermined US interests and brought the superpowers to the brink of war. This work exposes Reagan's dedication to diplomacy and his unorthodox views about global security, which frequently brought him into conflict with his own advisers and allies. The president did not seek to destroy the USSR; rather, he sought to eliminate nuclear weapons. This volume also explains why Moscow chose to abandon the arms race, adopt democratic reforms, and withdraw from its ill-fated war in Afghanistan. These initiatives were part of a reform movement that had been growing in the USSR for decades before Reagan entered office. The Kremlin did not acquiesce to American pressure; rather, Soviet reformers believed the arms race had been futile and sought to move beyond the Cold War. In fact, President Reagan's initially aggressive policies had made it more difficult for Moscow to pursue these revolutionary reforms. Ultimately President Reagan and General Secretary Gorbachev together were able to accomplish what no one at the time thought possible -- the peaceful conclusion of the Cold War. The president's opposition to nuclear weapons, his determined leadership, and his dedication to diplomacy are his most enduring legacies"--